Fenomena Alih Fonem dalam Tuturan Bahasa Indonesia oleh Penutur Bahasa Makassar di Desa Mangempang Kecamatan Bungaya Kabupaten Gowa - Muhammad Saeful; Syekh Adiwijaya Latief; Muhammad Dahlan (Jurnal Riset Rumpun Ilmu Bahasa, 2024)
This study aims to describe and analyze the phenomenon of phoneme transfer in Indonesian speech by Makassar speakers in Mangempang Village, Bungaya District, Gowa Regency. It focuses on identifying types of phoneme changes—substitution, omission, and addition—resulting from interference by the Makassar language as the speakers’ mother tongue. This research uses a qualitative descriptive method. The data consist of words or phrases uttered by Makassar speakers when using Indonesian, which reflect phonological variation. Data were collected through observation, recording, and note-taking techniques. Analysis techniques include identification, classification, description, and conclusion drawing. The results show that three types of phonological variation were identified. In terms of substitution, phoneme changes include: /k/ to /s/, /b/ and /k/ to /t/, /i/ to /e/, /l/ to /k/, /f/ to /p/, and diphthongs /ai/ to /e/ and /au/ to /o/. Additions include inserting a glottal stop [?] at word-final positions, adding /n/ and /m/ to form /ng/, and lengthening or emphasizing syllables. Omissions involve abbreviations, dropping certain phonemes, or replacing them with different sounds. These findings illustrate how native language interference affects the phonological structure of Indonesian spoken by the Makassar-speaking community in this region.